Intelligent dynamic bandwidth allocation algorithm in upstream EPONs - Radzi N.A.M. (2023)
An upstream access scheme for Ethernet passive optical networks, called the intelligent fuzzy-logic-based dynamic bandwidth allocation algorithm (IFLDBA) has been proposed. The algorithm provides the allotment of bandwidth between optical network units (ONUs) and within ONUs. Fuzzy logic is used to improve the bandwidth allocation within each ONU. We compare the IFLDBA algorithm with the existing broadcast polling algorithm. The results show that IFLDBA has bandwidth utilization of up to 21% better and lower delay than the broadcast polling algorithm. 2010 Optical Society of America.